ҲАЙНРИҲ ҲАЙНЕНИНГ “ҚАРАҒАЙ“ ШЕЪРИ ВА УНИНГ ТАРЖИМАЛАРИ ҲАҚИДА (Scientific journal of the Fergana State University, 2023)
In this article the famous German poet H. Hayne’s poem “Pine-tree” and its translations are highlighted. This poem is not about sweet hearts rather about single helpless pine-tree’s difficult situation is analyzed comparatively.